PENGARUH METODE PICTURE AND PICTURE TERHADAP BERPIKIR KREATIF SISWA SEKOLAH DASAR - Laily Husniyah Mabruroh (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
Creative thinking is an ability that can be used to develop their potential to face the challenges of the 21st century. Elementary school students must have creative and innovative ideas related to knowledge. The purpose of this study was to determine the effect of the method of picture and picture on the ability to think creatively. The population is the fifth grade students of SD Hang Tuah 10 Juanda. Through a simple random sampling technique, students selected class V-A as the control class and class V-F as the experimental class. This research is a quantitative study with a Quasi Experimental Design-Posttest Only Control Group research design. The data collection method uses a test. The test data of creative thinking skills were analyzed by means of different mean tests. The results showed that there was an influence of the picture and picture method on students' creative thinking abilities